Effect of nitrogen and organic manure on performance of hybrid napier (Pennisetum purpureum Schum.) and soil properties - SHARMA, ANIL KUMAR; SHARMA, A. K.; RAI, P. K.; BHARAT, RAJEEV (Journal of Soil and Water Conservation, 2017)
An experiment was conducted during 2006 to 2007 at the seed multiplication farm of SKUAST-J at KVKJammu to study the effect of different levels of farmyard manures and nitrogen application at different planting dates on the growth and forage yield of hybrid napier (Pennisetum purpureum Schum.). Significant increase in herbage yield on fresh and dry weight of hybrid-Napier was recorded when it was planted on 2nd March. Application of farmyard manure @ 20t/ha and increasing nitrogen levels from 40 to 80 kg/ ha resulted in significant increase in herbage yield (on both fresh and dry weight basis), NPK uptake and physico-chemical properties of soil. Napier-hybrid planted during first week of March in association with FYM@ 20 t/ ha and application of nitrogen @ 80 kg/ha was the most economical treatment and resulted in improved herbage yield on both fresh and dry weight basis. However, content of soil organic carbon showed a significant increase under different FYM levels. Among the different treatments, FYM application under various treatments recorded maximum available N, P and K in comparison to different levels of N application. In general, availability of K under different levels of FYM and other treatments showed its reduction.